Luto materno: dor e enfrentamento da perda de um bebê - Beatriz Gonçalves Lopes; Pollyanna Kássia de Oliveira Borges; Clóris Regina Blanski Grden; Carlos Eduardo Coradassi; Cibele de Moura Sales; Nauristela Ferreira Paniago Damasceno (Rev Rene, 2017)
Objective : to understand how mothers experienced the experience of their babies’ mourning. Methods : this is a qualitative study, conducted with nine mothers who experienced the loss of a child under one year. Semi- structured interviews were conducted, and the reports were organized using the Collective Subject Discourse. Results : the participants indicated the complexity and difficulties of the mourning process, implying a grief that lasted but could be overcome through spirituality and family support. They also showed the lack of support from the health services. Conclusion : although mourning is a complex and peculiar process, the mothers pointed out the importance of the spirituality and support of their relatives, but highlighted the lack of support from the health services.